Agriculture project as an economic development tool to boost socio-economic level of the poor community: the case of Agropolitan project in Malaysia - Mohamed Shaffril, Hayrol Azril; Abdul Nasir, Ahmad Faiz; Idris, Khairuddin; Uli, Jegak; Alby, Jeffrey Lawrence D'Silva (Academic Journals, 2010)
This paper is regarding Agropolitan projects and its potential in uplifting the community socio-economic level at Gahai Agropolitan project in Kuala Lipis, Pahang. The Agropolitan Programme were the Malaysian Government initiative to eradicate poverty in Malaysia. Regarding to this study, it is important to look at the planning of the programme before its potential can be clearly seen. The research approach for this study was a qualitative case study that provided in-depth descriptions of Agropolitan planning process in Malaysia. Data were gained through four in-depth interviews with the help of an interview guide with the officers who are related directly to the program planning of Agropolitan projects. The questions served as a guide, but allowed respondents freedom and flexibility in their answers. Data from the interviews were transcribed verbatim and subsequently analyzed by identifying similarities and consistent themes. The Ministry of Rural and Regional Development and the National Implementation Directorate are the backbone of this project. The project was then implemented by Land and Regional Development Unit, Ministry of Rural and Regional Development with an appointed organizer, Rubber Industry Smallholder Development Authority. Close relationship between the planner, implementer, organizer, and also the project participants would develop a power to strengthen the project and success in the future.